Panduan Moral Generasi Digital: Membumikan Akhlak Pribadi dari Bait Syi’ir KH. Bisri Mustofa - Zaid Munawar; Muhammad Yasin; Muhammad Fatchul Huda; Masyhuri Masyhuri; Hery Cahyono (Universitas Al Azhar Indonesia, 2026)
This research is motivated by the widespread decline in morals and identity crises among the younger generation due to the negative impacts of the digital era and global culture. As an effort to revitalize Islamic ethics based on local wisdom, this study aims to reconstruct the concept of morals toward oneself across the manuscript trilogy by KH. Bisri Mustofa Rembang (Ngudi Susilo, Mitra Sejati, and Washoya al Aba’ lil Abna’). This library research applies a philological approach to examine the texts and intertextual analysis to connect their core messages. Data were gathered through close reading and analyzed using content analysis combined with interpretative hermeneutics. The results show that KH. Bisri Mustofa's personal ethical system beautifully balances physical maintenance (outer discipline) and spiritual purification (inner purity). This concept manifests in four daily dimensions: health care, holistic cleanliness, physical grooming, and modest, polite attire. In the modern era, this concept transforms into a practical guide for thrifty financial management and a wise moral filter to navigate technological advancement without losing religious devotion. This classic pesantren trilogy remains highly relevant as a moral compass for the younger generation in the digital era.Keywords - Digital Disruption, KH. Bisri Mustofa, Morals Toward Oneself, Pesantren Manuscripts.